Evaluation of Medication Adherence in Patients with Type 2 Diabetes Mellitus: A Mixed- Methods Approach - Varghese Divya; Sr Deepthy (Bijimol NJ) (International Journal of Community Health Nursing And Practices, 2025)
Background: Medication adherence refers to how closely an individual follows the prescribed medication regimen. It is essential for achieving desired therapeutic outcomes and improving patient health. Inadequate adherence can result in the deterioration of health conditions, higher mortality rates, and increased healthcare expenses. Diabetes mellitus, being a chronic condition, demands ongoing medical care not only to prevent the onset of serious complications but also to manage them effectively once they arise. A high level of adherence to diabetic medications is necessary, however, it is good to be checked, and finding out various factors contributing to low adherence is mandatory to reduce patient morbidity and mortality. Objectives: (1) To assess medication adherence among people diagnosed with diabetes mellitus. (2) To explore the lived experiences of people diagnosed with diabetes mellitus. (3) To determine the association of medication adherence with selected baseline variables. Methods: The study employed an explanatory sequential design as its research framework. The sample consisted of 100 participants, who were chosen using a purposive sampling technique. Data was collected using a proforma to elicit baseline variables and a semi-structured checklist regarding medication adherence to diabetes. Among 100 samples, 17 samples were reported to have a low level of medication adherence, and they were invited to be a part of an in-depth interview, where data saturation was attained at the 8th sample. Results: In the quantitative arm, the majority of participants (53%) were aged 51–70 years, with 56% being female, 47% having a normal body mass index (BMI), and 41% having a high school education. Most were unskilled workers (46%) and married (96%), with 31% earning a monthly income of Rs.2391–7101. The majority (63%) were using one anti-diabetic drug, and adherence was medium in 48%, high in 35%, and low in 17%. A significant association was found with occupation, but no associations were observed with age, gender, education, income, marital status, BMI, or medication use. In the qualitative arm, key themes identified included perceived challenges (mood changes, fear of side effects), financial constraints (low prioritization, high medication costs), alternative therapies (home remedies, Ayurvedic treatments, weight reduction exercises), lack of knowledge (inadequate healthcare guidance, confusion due to social media), and self-management (diet adaptation, self-regulation of medications, irregular follow-ups). Interpretation and Conclusion: Out of 100 samples from the urban population, 17% had low adherence. This mixed-method study highlights the importance of understanding both the quantitative and qualitative aspects of medication adherence in type 2 diabetes mellitus (T2DM) patients. By tackling the identified obstacles and utilizing the facilitators, healthcare providers can create more effective approaches to boost adherence, leading to better patient outcomes.
Keywords: Medication Adherence; Mortality rates; diabetes mellites; lived experiences; self-management